Antecedent factors of maternal identity among primiparous Thai teenage mothers - Suphawadee Panthumas; Wirin Kittipichai; Kanittha Chamroonsawasdi; Pimsurang Taechaboonsermsak (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - Maternal identity (MI) is the attainment of maternal role adaptation. Though the role of the motherhood is expected to be achieved, teenagers, who are still developing their personal identity, do not always clearly identify or align with their role of motherhood. The purpose of this paper is to determine the structural relationship among a set of variables, infant temperament (IT), strain (ST), social support (SS), self-esteem (SE) and balanced family functioning (BF) influencing MI and to test the model using the empirical data. Design/methodology/approach - A cross-sectional survey was conducted among 353 primiparous Thai teenagers of infants aged 4-12 months. A self-administered questionnaire comprised six scales with Cronbach's α coefficients ranging from 0.81 to 0.93. The structural equation modeling method was employed to test the validity of the model undertaken using Mplus Software. Findings - The model fit the empirical data well (χ2/df=2.17, CFI=0.92, TLI=0.91, RMSEA=0.06, SRMR=0.05). The MI could explain 62 percent of the variance through its set of variables. Three antecedents, i.e. IT, ST and SS, had a direct effect while SE and BF had an indirect effect on MI. The IT had the highest total effect on the MI, while ST was a mediator among other study antecedences concerning the MI. Originality/value - The model adequately fit the data among teenage mothers one-year postpartum. Promoting MI should strongly diminish strain and encourage positively perceived infant temperament, self-esteem, social support and balanced family functioning.